MAKNA BUDAYA DALAM MITOS DI MINAHASA (MEANING OF CULTURE IN MYTHS IN MINAHASA) - Nontje Deisye Wewengkang (Kadera Bahasa, 2018)
Myth is a medium of understanding and inheriting cultural values that are believed by society in the past and also influences people’s mindsets in the present. In this study, myth is a reflection of social structures and social relations in which there are basic feelings commonly shared by human beings, such as love, , or revenge. This study aims to (1) describe the mythical myths Minahasa and (2) express the cultural meanings of the Minahasa people contained in Minahasa myths. The benefits of this study are in the form of disclosing the concepts of cultural meaning possessed by the Minahasa tribe so that they can broaden the horizons of thought about Minahasa society and culture. The method used in this study is the expository description method. Lévi-Strauss states that myths are formed by units of basic elements, in which the basic element units have a dual structural structure, namely historical and ahistorical at the same time whose elements are combined or connected to one another to produce meaning.